“I’m not gonna answer that”: A Critical Discourse Analysis of the Hawley-Zuckerberg Debate - Rahman, Fadhlur; Nuzulia, Rahma (UIN Sunan Gunung Djati Bandung, 2025)
The widespread use of social media has had a significant impact on digital power dynamics and accountability. Meta, the parent company of Facebook, Instagram, and WhatsApp, has frequently faced criticism for its social responsibility in addressing the detrimental effects of its platforms. Arguments between Senator Josh Hawley and Meta CEO Mark Zuckerberg during a US congressional hearing exemplified this tension. This study employs a Critical Discourse Analysis (CDA) approach based on Norman Fairclough's model, which has three main dimensions: text analysis, discursive practice analysis, and social practice analysis. This analysis demonstrates how Senator Josh Hawley and Mark Zuckerberg's debate at a US congressional hearing highlighted the tension between technological innovation and Meta-corporate social responsibility. Also, it emphasizes how Zuckerberg's apology lacked concrete steps in response to this issue, as he did not mention compensation for victims or major changes to the platform's algorithm. Hawley utilized hostile speech (aggressive or antagonistic, frequently with the intention of eliciting a negative response) to pressure Zuckerberg to admit Meta's failure to protect users. Ina contrary, Zuckerberg preferred defensive language (respond defensively, frequently in a manner that prevents open dialogue or hinders understanding) to project a positive picture of the corporation.